Pelatihan Accounting Games Sebagai Sarana Peningkatan Dasar Literasi Akuntansi Pada Generasi Milenial dan Zoomer - Prasetiyo, Yudhi; Widiastuti, Yeni; Wisnantiasri, Sila Ninin; Paramitha, Diky; Nugraheni, Novita; Dwirini, Dwirini; Zuhroh, Shufia (Universitas Terbuka, 2024)
The importance of learning about accounting knowledge from the start is the right step in preparing prospective accountants in the future. The importance of learning accounting using the game method has a good impact and response to the millennial generation in terms of increasing their financial literacy in carrying out economic activities. This training was carried out with the aim of increasing knowledge of accounting and financial literacy to prepare the millennial generation who are ready to become accountants in the future. This community service is carried out at Dharma Karya High School (SMA). The target audience for this training is grade 12 students with a concentration in social sciences. This training method is carried out offline using game accounting media as a tool for carrying out mentoring and training for class 12 students at SMA Dharma Karya. The results of this training were that Class 12 High School students with a concentration in social sciences were happier and were able to capture learning in the field of accounting to capture the absorption capacity related to accounting and financial literacy. Then in this training the participants' enthusiasm became higher and enthusiastic because the method used could make students' thinking about accounting easier and lighter, compared to learning using the text book method. With this training, overall participants can capture learning and increase accounting literacy more quickly and easily.